Gerencia Estratégica de costos en las Microempresas de la provincia de San Martín - Sánchez Sangama, Miguel Ángel (2011)
In the present research is discussed as a strategic management in micro costs of the Province of San Martin. The study surveyed regarding the value chain, strategic positioning and the causal or cost drivers, being that to achieve the objectives of the investigation. We identified a sample of 113 micro-enterprises in the province of San Martin, selected at random. lt was demonstrated that the studied companies gain a competitive advantage through continuous monitoring in the production process (industrial), mediation (commercial) and service delivery (service), which ensures the quality of the product (good or service). Its disadvantage lies in the gap in time management which generates unnecessary costs. Also it was observed that there are activities that do not generate value to the product and also have high costs and cause failures in the process. Moreover, they have a clear distinction between a strategy and another; the definitions of cost leadership and differentiation are studied in their completion.